A crossed-disciplinary evaluation of parental perceptions surrounding pediatric non-invasive brain stimulation research. Issue 4 (31st August 2020) - Behan, Michael; Nawshin, Tanjila; Nemanich, Samuel; Kowalski, Jesse; Sutter, Ellen; Francis, Sunday; Dubinsky, Janet; Freese, Rebecca; Rudser, Kyle; Gillick, Bernadette
Abstract : Purpose: Recruitment for pediatric non-invasive brain stimulation (NIBS) studies is often challenged by low enrollment. Understanding parental perceptions regarding NIBS is crucial to develop new communication strategies to increase enrollment. Design/methodology/approach: Integrating a crossed-disciplinary approach, the authors conducted a survey at the 2018 Minnesota State Fair querying the perception of risk and preferences of current and future parents associated with pediatric NIBS research. The survey consisted of 28 closed-text questions including demographics, photographs portraying NIBS, terminologies and factors related to NIBS studies. Findings: Complete surveys were analyzed from 622 parent participants. A significant number of participants (42.8%) perceived the photographs of NIBS as "risky." Additionally, 65.43% perceived the term "Non-invasive brain therapy" as not risky, a word combination not currently being used when recruiting potential participants. Over 90% (561/622) of participants chose the photograph of child-friendly MRI suite. Research limitations/implications: Although this survey identified aspects crucial in recruitment for pediatric NIBS research, there were limitations. For example, the authors did not record the sex or demographic distribution (e.g. rural versus urban setting) of the participants. These factors may also influence recruitment messaging. Originality/value: For important medical research to impact and improve the lives of the potential remedies, participation by the public in clinical trials is necessary. Often the general public perceives the trials as risky as a result of poor marketing communication recruitment material. This study sought to be understood if how the message is encoded has an impact on the decoding by the receiver.